Parents' preferences towards certain media of instruction for the public elementary schools of Manila - Condez, Regina (Resano) 1941- (s.n.], 1969)
The objective of the study is to determine the preferences of parents towards certain media of instruction for the public elementary schools of Manila with the aim of determining the medium in which the elementary grade pupils will be most benefited.